Boards of directors in sports associations in the Sultanate of Oman: between election and appointment - Al-Droushi, Abdul Rahim; Almuskery, Bader; Hadadi, Atia (Journal of Physical Education, 2023)
This study aims to identify the best successful models in selecting boards of directors of sports bodies (appointment, appointment and elections together, and elections) from the point of view of those belonging to the sports sector in the Sultanate of Oman. The study also reveals the statistically significant differences in the responses of the study’s sample. The study was carried out through a descriptive approach. The researchers designed a questionnaire consisting of three main dimensions to measure the study sample’s viewpoint on the three systems. The sample consisted of 193 participants who belonged to the sports sector in the Sultanate of Oman. The results show no consensus among the sample about the appropriateness of the three systems for selecting boards of directors in the sports federations in Oman. Nevertheless, the elections system, appointments, and elections together were less favorable than appointments that received higher acceptance. The study recommended investigating the causes that contributed to the fall of popularity and acceptance of elections as an essential system in electing sports boards of directors in the Sultanate of Oman. It is also recommended to evaluate the election experience during the past decades and develop regulations that contribute to the production of more effective boards of directors and the ability to develop organizational performance in the various sports bodies in the Sultanate of Oman.